Energy and budget balances for sweet potato-based ethanol production - Silva, Luis Felipe Lima e (2019)
The objective of this work was to assess the viability of sweet potato (Ipomoea batatas) for ethanol production, as well as to estimate the energy and budget balances for the crop. Data from the agricultural and industrial production phases were evaluated. Those from the agricultural phase were estimated from a field experiment and used for comparison of sweet potato genotypes. Those from the industrial phase were estimated based on the literature on the fossil fuel energy and electricity consumed in the ethanol production process. With average yields of 35 Mg ha-1 roots and 12 Mg ha-1 dry stems, the output/input ratios were 6.64 and 1.93 for the energy and budget balances, respectively. For yields of 50 and 80 Mg ha-1 roots (17 and 27 Mg ha-1 dry stems, respectively), the indexes for energy balance were 7.16 and 7.68, respectively, and those for energy budget were 2.76 and 4.42. The obtained results confirm the great aptitude of the sweet potato crop for biofuel production.